Об оценке эффективности многопроцессорных вычислительных систем - Полумиєнко, С.К.; Федюков, Д.А. (Екологічна безпека та природокористування, 2009)
The general review of methods of construction of the cluster systems is inprocess conducted, basic directions of their forming, and also tasks, arising up in the process of increase of efficiency or optimization of their functioning, are selected.